Karakteristik Kepemimpinan Transformasional di Madrasah Ibtidaiyah (MI) serta Relevansinya dengan Visi Pendidikan Abad 21 - Muhammad Shaleh Assingkily; Mesiono Mesiono (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2019)
This paper discusses the characteristics of transformational leadership in Islamic Elementery School (MI). It focuses on how the basic concepts of this kind of leadership are relevant to the 21st century education vision, on the what are the essential steps of a transformational leader on investigaties the strengths and weaknesses of transformational leadership in developing the quality of human resources in managing a school. This research used a qualitative approach with the main data of a literary study. The results of this research indicate that (1) the characteristic of transformational leadership through idealized influence, inspirational motivation, intelectual stimulation, and individual consideration (4I) are relevant to the vision of 21st century education. The characteristics are built in the form of life and career skills, learning and innovation skills, information, media, and technological skills, (2) the steps for a transformational leader to face the vision of 21st century education are described in the concept of 4I which is combined with 4C (critical thinking and problem solving, creativity and innovation, communication, and collaboration) towards 3 vision of education in the 21st century, and (3) the advantages of transformational leadership are in cost savings, high commitment, actualization of the potential human resources, and interpersonal communication, while the weaknesses are that it requires a relatively longer time, uneven empowerment, needs intense attention, and is difficult to apply to members in the number of units.